Composite hollow fiber membranes of modified zeolite Y for biogas upgrading. (2020) - Wichidit, Thakorn; Faungnawakij, Kajornsak; Klaysom, Chalida
Abstract: Biogas production has been globally promoted due to the need for renewable energy. Membrane gas separation is one of the most potential technologies for separating impurity and inert gases from the biogas to meet the fuel standard. Membranes with high selectivity and high permeability are most desirable in membrane gas separation. This study aims to develop the composite hollow fiber membrane for CO2 separation from CO2 /CH4 mixture. The synthesized composite membranes were composed of a support layer of polysulfone (PSF) and a selective layer, containing poly-block-amide (PEBAX1657) and modified zeolite Y as the filler. The effects of filler loading at 0, 5, 10, 15, and 20 on membrane properties and performance were investigated. The defect-free composite membranes were successfully obtained in all filler loadings.